Between fruit variability of the bioactive compounds, β‐carotene and mangiferin, in mango (Mangifera indica). Issue 2 (29th January 2013) - Hewavitharana, Amitha K.; Tan, Zhi W.; Shimada, Ryo; Shaw, Paul N.; Flanagan, Bernadine M.
Abstract: Aim: As the use of nutraceuticals has become increasingly popular, there is now a general interest regarding the amount of fruit one must consume in order to fulfil the recommended intake of a particular bioactive. Consequently, the variation in the amount of bioactive between apparently equivalent (variety, maturity) fruits has become an important factor to consider. The present study is conducted to principally address the variation of bioactives between fruits, which has received scant attention in the literature. Methods: Kensington Pride mangoes were chosen as the fruit of interest and two signature bioactive compounds, β‐carotene and mangiferin representing two extreme polarities, were chosen to study inter‐ and intra‐fruit variability. Visible spectrometry and HPLC‐tandem mass spectrometry were used to measure the compounds. Results: The intra‐ and inter‐fruit variability of mangiferin content was found to be 12.7% and 139%, respectively (n = 10). The intra‐fruit variability of β‐carotene was 2.57%, while the inter‐fruit variability was 38.5% (n = 10).